Cultured fish diseases in Basrah province for the years 2014, 2015 and 2016 - Jassim , AbdulAmer R. (Iraqi Journal of Aquaculture, 2023)
During this study, 95 disease cases were recorded, 40 of them were due to the bacterial gill disease, 29 due to the skin ulcer disease, 14 due to the intestine inflammatory disease and nine cases of Asian tapeworm Schyzocotyle acheilognathi, one case each of acidity disease, high ammonia disease and fin rot. Health problems were recorded in 71 fish farms for the three years in an epidemiological or mass infections which included 46 pond farms with a total area of ​​310 dunam (0.25 ha) and 15 fish farms with a total of 139 cages and a total area of ​​1733.2 m2. Infected farms that adopt closed and semi-closed systems were 10 farms with a total area of ​​1233.2 m2. Death rates were different. The highest incidence of disease (52 cases) was recorded in 2016. Cases were described, the causes of the diseases and the results were recorded based on the chronological sequence of each case, type of infection and method of fish farming.